Quality Tourism: Tourism Development and Improvement Strategies In Indonesia’s Super Priority Destinations - Mahmudin, Tono; Sirait, Evi; Satmoko, Nugroho Djati; Mistriani, Nina; Harahap, Muhammad Ade Kurnia (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine (1) the potential for quality tourism in Indonesian Super Priority Destinations; and (2) tourism development and improvement strategies in Indonesian Super Priority Destinations through quality tourism. This research is qualitative-descriptive research. The data analysis technique used in this research is SWOT analysis. The results of this research show that (1) the potential of Super Priority Destinations is not only to attract tourists but also to foster a creative economic ecosystem that involves local residents; and (2) the strategy for developing and building quality tourism in Indonesian Super Priority Destinations includes the SO strategy by planning tourism development and improvement through infrastructure improvements and promotions to create quality tourism, the WO strategy by offering the concept of quality tourism in super priority destinations (improving the quality of human resources) , the ST strategy through collaboration with stakeholders supports Quality tourism in Indonesia's super-priority destinations, and the WT strategy evaluates the promotion of super-priority destinations and attracting investors.